IgA antibody response in acute rubella determined by solid-phase radioimmunoassay. - Halonen, P. (Cambridge University Press, 1979)
A solid-phase radioimmunoassay (RIA) for detecting rubella virus IgA serum antibodies was developed. Purified rubella virus grown in roller cultures of Vero cells was adsorbed onto polystyrene beads. The coated beads were then incubated with dilutions of serum, and rubella IgA antibodies which attached to the virus antigen on the solid-phase were subsequently detected with 125I-labelled anti-human-alpha antibodies. The specificity of the iodinated anti-human immunoglobulins was confirmed by RIA analysis of fractions obtained by chromatography of an early convalescent serum on an agarose column. A complete separation of IgM, IgA, and IgG was observed. A total of 144 serial serum specimens from 31 adult patients with an acute rubella infection were tested for rubella IgA antibodies, and the results were compared with the RIA IgG and IgM titres reported earlier from the same specimens. The RIA IgA response was detected in each of the 31 patients and the IgA antibodies appeared almost simultaneously with the IgG and IgM antibodies. The maximum titres, which were lower than the IgG and IgM titres, were reached in about 1 week after the onset of rash. In 6 patients out of 31 the IgA antibody response was transient and persisted approximately two months, while in the remaining 25 patients the IgA antibodies persisted throughout the study period of more than 5 months. The results obtained indicate that the presence of rubella IgA antibodies in serum is not an indication for a recent rubella infection.